Cysteine Cathepsins and Their Prognostic and Therapeutic Relevance in Leukemia - Arora, Mohit; Pandey, Garima; Chauhan, Shyam S. (Annals of the National Academy of Medical Sciences (India), 2021)
Cysteine cathepsins are lysosomal proteases that require Cys-His ion pair in their catalytic site for enzymatic activity. While their aberrant expression and oncogenic functions have been widely reported in solid tumors, recent findings suggest that these proteases also play an important role in the pathogenesis of hematological malignancies. In this review, we summarize the potential clinical implications of cysteine cathepsins as diagnostic and prognostic markers in leukemia, and present evidences which supports the utility of these proteases as potential therapeutic targets in hematological malignancies. We also highlight the available information on the expression patterns, regulation, and potential functions of cysteine cathepsins in normal hematopoiesis and hematological malignancies. In hematopoiesis, cysteine cathepsins play a variety of physiological roles including regulation of hematopoietic stem cell adhesion in the bone marrow, trafficking, and maturation. They are also involved in several functions of immune cells which include the selection of lymphocytes in the thymus, antigen processing, and presentation. However, the expression of cysteine cathepsins is dysregulated in hematological malignancies where they have been shown to play diverse functions. Interestingly, several pieces of evidence over the past few years have demonstrated overexpression of cathepsins in leukemia and their association with worst survival outcomes in patients. Strategies aimed at altering the expression, activity, and subcellular localization of these cathepsins are emerging as potential therapeutic modalaties in the management of hematological malignancies. Recent findings also suggest the involvement of these proteases in modulating the immune response in leukemia and lymphomas.
Keywords: cathepsins; leukemia; proteases; acute myeloid leukemia; CTSL; CTSB